In Situ Polymerized 1,3-Dioxolane Electrolyte for Integrated Solid-State Lithium Batteries - Mi, Ye Qian; Deng, Wei; He, Chaohui; Eksik, Osman; Zheng, Yi Ping; Yao, De Kun; Liu, Xian Bin (Wiley-V C H Verlag Gmbh, 2023)
Solid-state lithium batteries are promising and safe energy storage devices for mobile electronics and electric vehicles. In this work, we report a facile in situ polymerization of 1,3-dioxolane electrolytes to fabricate integrated solid-state lithium batteries. The in situ polymerization and formation of solid-state dioxolane electrolytes on interconnected carbon nanotubes (CNTs) and active materials is the key to realizing a high-performance battery with excellent interfacial contact among CNTs, active materials and electrolytes. Therefore, the electrodes could be tightly integrated into batteries through the CNTs and electrolyte. Electrons/ions enable full access to active materials in the whole electrode. Electrodes with a low resistance of 4.5 omega (-1) and high lithium-ion diffusion efficiency of 2.5x10(-11) cm(2) s(-1) can significantly improve the electrochemical kinetics. Subsequently, the batteries demonstrated high energy density, amazing charge/discharge rate and long cycle life.
Keywords: Interface; Lithium Battery; Polymerization; Solid-State Electrolyte